Cabozantinib and Axitinib After Vascular Endothelial Growth Factor Therapy in Patients with Advanced Renal Cell Carcinoma: A Retrospective Cohort Study from England - Janet Brown; Brooke Harrow; Anne Marciniak; Christine McCarthy; Aude Houchard; Lori Cirneanu; Andrew Protheroe (Adis, Springer Healthcare, 2024)
Abstract Background and Objective The tyrosine kinase inhibitors cabozantinib and axitinib have been widely used in England to treat advanced renal cell carcinoma following prior vascular endothelial growth factor-targeted therapy, but data on real-world usage remain limited. Our objective was to describe the real-world treatment patterns and outcomes of patients with advanced renal cell carcinoma who received second-line or later-line (≥ 2L) cabozantinib or axitinib after vascular endothelial growth factor-targeted therapy in clinical practice in England. Methods This retrospective cohort study used clinical practice data (collected 2011-20) from the English Cancer Analysis System database. Patient characteristics, treatment sequence and duration, and overall survival (time from initiation of cabozantinib/axitinib treatment to death) were evaluated. Results Data from 1485 eligible adults with advanced renal cell carcinoma were analyzed: 440 received ≥  2L cabozantinib (2L for 88.6% of them); 1045 received ≥  2L axitinib (2L for 89.5%). The most common first-line treatments were sunitinib (2L cabozantinib subcohort, 48%; 2L axitinib subcohort, 46%) and pazopanib (46% and 54%, respectively); nivolumab was the most common third-line treatment (18% and 19%, respectively). Median (interquartile range) 2L therapy duration was 5.52 (2.73-11.74) months for cabozantinib and 4.60 (1.45-12.36) months for axitinib. Following adjustment for potential confounders using inverse probability weighting, overall survival (median [interquartile range]) was longer for ≥ 2L cabozantinib (11.2 [5.7-28.0] months) than for ≥  2L axitinib (10.4 [4.7-22.0] months; log-rank p = 0.0034). Conclusions The Cancer Analysis System database is a valuable research resource providing extensive real-world clinical data. Real-world overall survival was longer with ≥  2L cabozantinib than with axitinib. Clinical Trial Registration ClinicalTrials.gov, NCT04637204; registered November 2020.